Structural Mechanism of TAF-Iβ Chaperone Function on Linker Histone H1.10. Issue 19 (15th October 2022) - Feng, Haniqao; Zhou, Bing-Rui; Schwieters, Charles D.; Bai, Yawen
Graphical abstract: Highlights: Human linker histone isoform H1.10 and its chaperone TAF-Iβ form a 2:2 complex. Structure of the H1.10-TAF-Iβ core complex from methyl NMR-spin label studies. H1.10 interacts with TAF-Iβ mainly through electrostatic interactions. TAF-Iβ functions as a chaperone by blocking the DNA binding sites of H1.10. Abstract: Linker histone H1, facilitated by its chaperones, plays an essential role in regulating gene expression by maintaining chromatin's higher-order structure and epigenetic state. However, we know little about the structural mechanism of how the chaperones recognize linker histones and conduct their function. Here, we used biophysical and biochemical methods to investigate the recognition of human linker histone isoform H1.10 by the TAF-Iβ chaperone. Both H1.10 and TAF-Iβ proteins consist of folded cores and disordered tails. We found that H1.10 formed a complex with TAF-Iβ in a 2:2 stoichiometry. Using distance restraints obtained from methyl-TROSY NMR and spin labels, we built a structural model for the core region of the complex. In the model, the TAF-Iβ core interacts with the globular domain of H1.10 mainly through electrostatic interactions. We confirmed the interactions by measuring the effects of mutations on the binding affinity. A comparison of our structural model with the chromatosome structure shows that TAF-Iβ blocks the DNA binding sites of H1.10. Our study provides insights into the structural mechanism whereby TAF-Iβ functions as a chaperone by preventing H1.10 from interacting with DNA directly.